Water Resource Management Options in the Seawater Irrigation Project in Kung Krabaen, Thailand - Tantisaowaphap, Somsak (1999)
The purpose of this study was fourfold as follows: Firstly, to elucidate problems related to shrimp culture in Kung Krabaen Bay. Secondly, to study trends in water quality in the Kung Krabaen Bay. Thirdly, to determine the perception of the shrimp farmers on a number of matters about the Seawater Irrigation Project, and finally to determine the most appropriate methods for managing the new water resource associated with the Seawater Irrigation Project. The methodology for the study consisted of field observations, questionnaire surveys, sampling and analysis of water and wastewater, and discussions with some relevant authorities and NGOs connected with the study. The field work was carried out from September 1996 to September 1997 in Kung Krabaen Bay. Sampling of water in the shrimp ponds was carried out over two cropping seasons with each crop consisting of ten ponds. Each water sample was analysed for Dissolved Oxygen, Biochemical Oxygen Demand, Nitrite, Nitrate, Ammonia, pH, Salinity, Water Temperature and Suspended Solids. The interview form was pretested in October 1996, improved, and real data was gathered beginning February 1997. A total of 88 respondents were used in the social survey. All data were then analysed for frequencies, means, standard deviation, and percentage. In addition, the t-test and one-way ANOVA were employed to compare water quality values.